Clinical Importance of Serum BDNF (Brain Derived Neurotrophic Factor) Level for the Management of Pregnancies Complicated with Meconium-Stained Amniotic Fluid - Firdaws Midhat Jihad; Esraa Abdulkareem Mohammed (Diyala Journal of Medicine, 2025)
Background: Meconium-stained amniotic fluid complicates pregnancies and is associated with high risk of neonatal meconium aspiration syndrome. Early detection of meconium-stained amniotic fluid is essential to prevent adverse neonatal outcomes. Objectives: To investigate the relationship between poor neonatal outcomes of meconium-stained amniotic fluid and serum brain-derived neurotrophic factor (BDNF). Patients and Methods: A case control study was carried out in the Department of Obstetrics and Gynecology of Azadi Teaching Hospital in Kirkuk, Iraq from 1st of March to 31st of August 2024 on a sample of 90 pregnant women. The case group included 45 pregnant women who underwent cesarean section due to fetal distress with meconium-stained fluid, and the control group included 45 pregnant women who underwent cesarean section due to fetal distress without meconium-stained liquor. The brain-derived neurotrophic factor was assessed in mothers and neonates from umbilical vein. Results: Mean maternal and fetal cord (brain-derived neurotrophic factor) level was significantly lower among pregnant women with meconium-stained liquor compared to controls (p<0.001). The maternal BDNF cutoff for predicting meconium-stained liquor fetal distress was 1.76 ng/ml, showing an acceptable validity finding with sensitivity 100%, specificity 95.6% and accuracy 98.5%. The maternal and fetal brain derived neurotrophic factor levels were positively correlated with birth weight and APGAR score at both 1 and 5 minutes in neonates from pregnancies complicated with meconium-stained liquor. Conclusion: Maternal and fetal cord serum brain-derived neurotrophic factors are decreased in fetal distress with presence of meconium-stained amniotic fluid. Keywords: Meconium-stained amniotic fluid, Fetal distress, Brain-Derived Neurotrophic Factor.